Winds and radiation in unison: a new semi-analytic feedback model for cloud dissolution - Rahner, Daniel; Pellegrini, Eric William; Glover, Simon; Klessen, Ralf S. (Monthly notices of the Royal Astronomical Society, 2017)
Abstract: Star clusters interact with the interstellar medium (ISM) in various ways, most importantly in the destruction of molecular star-forming clouds, resu
Published: 20 June 2017
Gesehen am 18.10.2018